The Involvement of Platelets and the Coronary Vasculature in Collagen-Induced Sudden Death in Rabbits - Mallarkey, G; Smith, G M (Thrombosis and Haemostasis, 1985)
The mechanism of collagen-induced sudden death in rabbits was studied by measuring blood pressure (BP), heart rate, ECG, the continuous platelet count and the plasma levels of thromboxane B2 (TxB2) and 6-keto prostaglandin Fia (6-keto PGF1α). Death was preceded by myocardial ischaemia and a sharp fall in BP which occurred before any fall in platelet count was observed. The calcium entry blockers (CEBs), verapamil, nifedipine and PY 108-068 protected the rabbits from sudden death without any significant effect on the decrease in the platelet count or increase in plasma TxB2 levels. 6-keto PGF1α could not be detected in any plasma samples. Indomethacin and tri-sodium citrate also protected the rabbits but significantly reduced the fall in platelet count and plasma TxB2. In vitro studies on isolated aortae indicated that verapamil non-specifically inhibited vasoconstriction induced by KC1, adrenaline and U46619 (a thromboxane agonist). It is concluded that CEBs physiologically antagonize the vasoconstricting actions of platelet-derived substances and that it is coronary vasoconstriction that is primarily the cause of death.
Keywords: Platelets; Thromboxane; Calcium entry blockers; Sudden death